Análise comparativa da ansiedade relatada em surdos e ouvintes - COSTA, Edilane Lourenço da (Universidade Federal do Pará, 2019)
The group of deaf people in Brazil is considered significant. Deafness can lead to emotional disorders, among them anxiety. Thus, the aim of this study was to measure anxiety reported among deaf and hearing people, with application of the Visual Analogue Mood Scale (VAMS) standard and adapted to Brazilian sign language. The sample consisted of 62 participants were divided into hearing group (n = 31) and deaf group (n = 31) mean age of 31 (±7.53) and 31 (±7.69) years, respectively, of both sexes, paired for age, sex, income and education level . The application of VAMS were individually and data were analyzed for factors: anxiety, physical sedation, mental sedation, other feelings and the total index scale. The data was preceded by the application of the normality test (Kolmogorov-Smirnov) and equal variance test. For data that obeyed these tests, we used the Student t test to compare the factors of VAMS; between groups, between male and female, within groups and between groups; at different income levels, within the groups and between groups; in different years of study, within groups and between groups. When it was not possible to satisfy the criteria of normality and homogeneity of variance test was used non-parametric Mann-Whitney (U). It was adopted a significance level of p ≤ 0.05. We analyzed the correlation in the variables, income, education level and age with each of the scale factors, in the hearing group and the deaf group. The results showed statistically significant difference between groups in the index of physical sedation, being lower in deaf than in the hearing group. In the analysis between groups, hearing and deaf, distributed by sex, was expressed statistically significant in the factor other feelings, being higher in the deaf, both females and males in relation to the male hearing group. In the variables income and education level were statistically significant differences in the components of VAMS, anxiety, mental sedation and physical sedation, between and within groups. In the correlation analysis, the hearing group, positive correlation was found in the variable income and education level versus physical sedation and positive correlation in the variable age versus anxiety. In the deaf group was a positive correlation in the variable age versus physical sedation. We conclude that the use of scales to assess anxiety is important and valuable for field research, and VAMS adapted to Brazilian sign language was sensitive to evaluate anxiety in deaf, it facilitates the inclusion diagnosis of this specific population, which is sometimes sub diagnosed.